Washback Effect of TOEIC Listening And Reading as a College Exit Test in Riau, Indonesia - Masrul Masrul; Ummi Rasyidah (UIBU, 2023)
The utilization of the TOEIC test in some universities in Indonesia as a language exit exam highlights the phenomenon of the washback effect, revealing that this exit requirement influences the narrowing of teaching content and a less communicative teaching process.Some universities in Indonesia have employed the TOEIC (Test of English for International Communication) listening and reading test as a language exit exam. This study investigated teachers’ perceptions concerning the TOEIC listening and reading test. The data were gathered by administering a questionnaire at three major Indonesian universities. The finding revealed that using TOEIC listening and reading as an exit requirement impacted the narrowing of teaching content and led to a non-communicative teaching process, yet the influence was not significant. This study found that the perceived test impact was influenced by factors differing from another research context.